Physical activity of female Malay Muslims before, during and after Ramadan - Soh, Kim Geok; Soh, Kim Lam; H., Ruby; J., Salimah (Africa Association for Health, Physical Education, Recreation, Sport and Dance, 2010)
Ramadan is the fasting month for Muslims, during which physical activities like sports may be held in abeyance for a more spiritual life. This researeh assessed the level of physical activity of female Muslim Universiti Putra Malaysia (UPM) staff during the month of Ramadan, and the factors affecting their activity. Fifty-four staff volunteered to participate in the study. They were asked to wear a pedometer (Yamex-Digi walker CW700) for five consecutive days before, during and after Ramadan. The mean number of steps taken dauy before, during and after were 6,716 ± 2,548, 5,829 ± 1,911 and 6,319 ± 2,418, respectively. All the figures were in the 'low active' class based on the standard by Tudor-Locke and Bassett (2004) in which a minimum of 10,000 steps a day denotes an 'active' lifestyle, deemed sufficient to confer health benefits to the individual. Nevertheless, there was a sigrdficant decrease between before and during Ramadan values, with F(2, 52) =3.44, p<.039. Thus, all the participants under-exereised throughout the month. The main factor restricting their physical activity was their lack of self-motivation (79.6%).